2020
DOI: 10.1299/mej.20-00215
|View full text |Cite
|
Sign up to set email alerts
|

Jet vectoring using secondary Coanda synthetic jets

Abstract: In recent years, studies on the fundamental principle of thrust vectoring using jets have been conducted to realize next-generation aircraft applications. Various methods for vector control of jet flow have been proposed, such as methods that achieve control via steady, continuous jets under the Coanda effect, steady suction flows near the Coanda surface, and synthetic jets from a neighbor slot as secondary jets. However, there are no studies on the flow direction control of jets using the secondary synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…In previous studies, although the "control region" (i.e., range in which the deflection angle can be treated as a function of the momentum coefficient) is narrow, it is effective to apply suction to the secondary flow to deflect the jet. As previously reported, 9,17,25) the results of this study correspond to the results obtained in the previous study.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…In previous studies, although the "control region" (i.e., range in which the deflection angle can be treated as a function of the momentum coefficient) is narrow, it is effective to apply suction to the secondary flow to deflect the jet. As previously reported, 9,17,25) the results of this study correspond to the results obtained in the previous study.…”
Section: Resultssupporting
confidence: 92%
“…Results for three ratios of steady-state velocity to velocity fluctuation amplitude, ¼ À1, ¹1, and 0, and dimensionless frequencies, f à ¼ 0:02, 0.05, and 0.08, are discussed. Similar to the results of Kobayashi et al, 25) it can be confirmed that the deflection angle c depends on both the momentum ratio ² and dimensionless frequency f à . Furthermore, it also clearly depends on the ratio ¦ between the steady velocity and velocity fluctuation amplitude, as previously described.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations